Barriers that affect the use of birth control options among women of reproductive age in Bwaise slum. A cross-sectional study. - Muderhwa Bacigale, Rodrigue (Student's Journal of Health Research Africa, 2022)
Background Ugandan women, on average, give birth to nearly two more children than they want, one of the highest levels of excess fertility in Sub-Saharan Africa. More than half of pregnancies in Uganda are unintended, and almost a third of these end up in abortions. The purpose of the study was to assess the barriers that affect birth control use among women of reproductive age in the Bwaise slum. Methodology A cross-sectional study design and systematic random sampling were used to reach 384 study participants. Data were collected using questionnaires through direct interviews. The Chi-square test was used to establish the hypothesis, the association between independent variables and the dependent variable was performed, and a p-value < 0.05 was accepted as statistically significant at 95% CI. Results Knowledge is universal (99.7 %). Each woman was aware of at least 2.7 birth control options on average, with 91.4% knowing at least one option and 86 % knowing at least one advantage of using birth control. About 66.4% of participants have ever used a birth control option, and at the moment of the survey, only 37.2% reported using a birth control option. Association between the use of birth control and knowledge about a facility with birth control services, distance to the facility, lack of money, previous experience of side effects, and religious discouragement were noted. Conclusion Women of childbearing age in the Bwaise slums used contraceptives below the national target of 50% with a high dropout rate. Side effects, lack of money, lack of knowledge of a facility, distance to the facility, and religious discouragements impact the use of birth control in the Bwaise slum. Recommendation: Active outreaches to relay comprehensive information about birth control options, involving women of childbearing age, and religious and cultural leaders in the Bwaise slum are needed.